High-Speed EMU TCMS Design and LCC Technology Research. (February 2017) - Zhao, Hongwei; Huang, Zhiping; Mei, Ying
Abstract: This paper introduces the high-speed electrical multiple unit (EMU) life cycle, including the design, manufacturing, testing, and maintenance stages. It also presents the train control and monitoring system (TCMS) software development platform, the TCMS testing and verification bench, the EMU driving simulation platform, and the EMU remote data transmittal and maintenance platform. All these platforms and benches combined together make up the EMU life cycle cost (LCC) system. Each platform facilitates EMU LCC management and is an important part of the system.